2021
DOI: 10.1002/anie.202103125
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Photon Near‐Infrared‐Responsiveness from the Molecular to the Supramolecular Level via Platination of Pentacenes

Abstract: Near-infrared (NIR) responsiveness is important for various applications.Currently,single-photon NIR-responsive systems are rare compared to systems that display two-photon absorption and triplet-triplet annihilation processes.S upramolecular stacking of photo-responsive chromophores results in decreased efficiency due to space-confinement effects. Herein we showt hat s-platination of pentacenes is af easible protocol to build single-photon NIR-responsive systems,w ith advantages including alow HOMO-LUMO ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…For example: Wang et al . reported some light‐responsive supramolecular polymers regulated from the molecular to the supramolecular level; [ 5‐6 ] Qin and Yang et al . reported some “turn‐on” photo‐switchable fluorescent metallacycles; [ 7‐8 ] Han et al .…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…For example: Wang et al . reported some light‐responsive supramolecular polymers regulated from the molecular to the supramolecular level; [ 5‐6 ] Qin and Yang et al . reported some “turn‐on” photo‐switchable fluorescent metallacycles; [ 7‐8 ] Han et al .…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…As previously reported, acenes and σ-platinated acenes undergo photo-induced endoperoxidation in the presence of oxygen (Supplementary Figs. 39 − 40 , 43 ) 40 , 41 . In this regard, we sought to modulate the sequential energy transfer process of 1 / 2/3 via photo-irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…We envisage that σ-platinated (hetero)acenes represent suitable candidates since various acene and heteroacene derivatives can be synthesized with broad spectral coverage 37 39 . These σ-platinated acenes are prone to aggregate with each other due to their structural similarity, guaranteeing the proximity of D/A pairs in the resulting supramolecular copolymers 40 42 . The Pt(II) units prevent severe stacking of (hetero)acenes to avoid aggregation-caused emission quenching, and thereby maintain sufficient emission intensity at the aggregated state.…”
Section: Introductionmentioning
confidence: 99%
“…These results revealed that the photochromic behavior of CIT-Z stems from the subtle molecular conformation variation of the TPE group. With the help of the Gaussian 16 43 software package, TD-DFT computations 35 were carried out using simulation of the absorption spectra of CIT-Z before and after UV-light irradiation. The crystal data for calculation were collected from the same crystal at the same position before and after irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical Computations. To elucidate the photochromic behavior of CIT-Z, time-dependent density functional theory (TD-DFT) 35 computations using the single-crystal data before and after UV-light irradiation were performed with the TPSSh functional. During TD-DFT computations, light elements (C, O, N, and H) were described by 6-311G* basis sets, while heavy atoms (Cu and I) were described by SDD.…”
Section: Methodsmentioning
confidence: 99%